2021
DOI: 10.1186/s13018-021-02817-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between type of anesthesia and length of hospital stay in primary unilateral total knee arthroplasty patients: a single-center retrospective study

Abstract: Objective This study explored the risk factors influencing the length of hospital stay (LOS) and establish whether the type of anesthesia is independently associated with the LOS in patients after primary unilateral total knee arthroplasty (TKA). Methods In this retrospective cohort study, 2309 patients undergoing unilateral TKA were recruited between January 2013 and June 2014 in a tertiary academic medical center in Singapore. Univariate and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…This is consistent with the findings of the present study. General anesthesia has been reported to prolong the length of hospital stay in patients undergoing unilateral TKA [ 20 , 21 ]; this is also consistent with our findings. However, contrastingly, some studies have shown that the method of anesthesia does not affect the length of hospital stay [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the findings of the present study. General anesthesia has been reported to prolong the length of hospital stay in patients undergoing unilateral TKA [ 20 , 21 ]; this is also consistent with our findings. However, contrastingly, some studies have shown that the method of anesthesia does not affect the length of hospital stay [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although general and local anesthesia, including spinal subarachnoid anesthesia, are suitable for TKA,, local anesthesia has been reported to shorten the length of hospital stay compared to general anesthesia [17][18][19] , which was consistent with the ndings of the present study. General anesthesia has been previously reported to prolong the length of hospital stay in patients undergoing unilateral TKA 20,21 , consistent with our ndings. However, contrastingly, some studies have shown that the method of anesthesia does not affect the length of hospital stay 22 .…”
Section: Related Factors Affecting the Length Of Hospital Staysupporting
confidence: 92%
“…Regional techniques for TAH are evolving and represent a relatively new indication for the use of RA, with either quadratus lumborum block 21 , superior hypogastric block 22 , or transversus abdominis plane block 23 . For this reason, it is not surprising for RA utilization rates to be lower for this relatively newer indication than for more established surgical indications such as TSA 24 and TKA [25][26][27][28] . In addition, a study Cozowicz et al 16 in 2016 documented the use of neuraxial anesthesia for TKA between 2006 to 2013 as 24.7%-21.3%, and the use of peripheral nerve blocks for TKA during the same time period as increasing from 10.3-20.4%.…”
Section: Discussionmentioning
confidence: 99%